EFFECT OF CONVOLVULUS PLURICAULIS EXTRACT ON CAFETERIA DIET INDUCED OBESITY IN MICE - Sharma, Abhishek; Verma, Hitesh; Yashwant; Prasad, Shyam Baboo (Innovare Journal of Life Sciences, 2013)
Objective To evaluate the anti obesity effect of extract of Convolvulus pluricaulis in mice feed with cafeteria diet Methods Obesity was induced in mice by feeding them a daily for fourty one days in addition to normal diet. Body weight and food intake was measured initially and then every week thereafter. On day fourty onefourty one serum biochemical parameter were measured and animal were sacrificed using overdose of ether. The liver kidney fourty one heart and spleen were removed and weighed immediately. Results may leads to obesity in mice however standard Sibutramine. Treatment with extracts of Convolvulus pluricaulis caused changes in the blood parameter including decease levels of total cholesterol TC fourty one low density lipoprotein cholesterol LDL C and TG but increased high density lipoprotein cholesterol Conclusion Methanolic extract of Convolvulus pluricaulis is a potential source of anti obesity phytomedicine. Keywords Antiobesityfourty one Convolvulus pluricaulisfourty one Shankhpushpifourty one Obesityfourty one Phytomedicine.